Asset Re-Functionalization To Build Business Empowerment In The Community Of Scavengers In The Landfill Of Njawar, Surabaya - Prasetijowati, Tri; Setyarahajoe, Ratna; Suminah; Sapja (Advances in Social Sciences Research Journal, 2019)
The increase in the number of urbanization in big cities such as in Surabaya has its own impact, especially, in the availability of employment in the formal sector and it leads to an alternative of choice to switch to the informal sector. Scavenging is one of the informal sectors that many migrants in urban areas are interested in. Although the community lives with the severe limitations, they are still able to survive and maintain their lives in the bug city, and strive to improve their standards of living. They have their own assets of physic, finance, human resources, and social capital although they are at a lower stage. That is why that re-functioning those assets is really necessary to create a model of business empowerment consisting of 3 dimensions, namely: the dimensions of business opportunities, HR development of scavengers, and accessibility of business resources. The dimension of business opportunities includes a proposal for compost processing, sorting, washing and milling of scavenging products, and savings and loans (cooperatives). Whereas, the dimension of HR development of scavengers include the patterns of scavenger imaging, increasing the security and order, improvement of life skills and social security. The dimension of accessibility of business sources includes partnering with the government and non-government institutions. Qualitative method was applied in this research, and technique of collecting data was conducted by using observation, interviews and Focus Group Discussion (FGD). Purposive sampling was implemented to get the samples. The empowerment would result in some positive outputs such as the increase of income, the building of a positive image of scavengers by removing the negative stereotypes, and the building of networks with the central and regional governments and non-governmental institutions.